Experimental Study on Sulfate Wetting–Drying Cycle of Metal Tailings Powder Concrete - Wu, Ruidong; Zou, Min; Liu, Juanhong; Zhang, Guangtian; Zhang, Yueyue (Frontiers in Materials, 2022)
In order to absorb a large amount of metal tailings powder and alleviate the shortage of mineral admixture in concrete, metal tailings powder can form a compound admixture with slag powder to prepare concrete. The sulfate wetting–drying cycle test of concrete with different contents of metal tailings powder was carried out to study the action law of metal tailings powder on the sulfate corrosion resistance of concrete. Scanning electron microscope, XRD, and nuclear magnetic resonance microscopic tests were used to reveal the deterioration mechanism of metal tailings powder concrete eroded by sulfate. The results show that proper addition of metal tailings powder can increase the sulfate corrosion resistance of C50 concrete. When the ratio of metal tailings powder to slag powder is 3:7 and 5:5, the sulfate corrosion resistance grade can reach KS180. There is a strong linear relationship between the relative ultrasonic velocity factor and relative compressive strength factor. The sulfate failure mechanism of metal tailings powder concrete is mainly the internal formation of corrosion products ettringite and gypsum. The introduction of metal tailings powder can reduce the alkalinity of concrete and improve the pore structure, thus improving the sulfate corrosion resistance of concrete.